Estudio de prefactibilidad para la instalación de una planta productora de bebida instantánea en polvo a base de cereales andinos - Peredo Paredes, Pastor Jose Antonio (2019)
Nowadays, Lima society is adopting new consumption habits, increasingly healthy, nutritious and natural; this is due to the global trend to eat healthy and avoid consuming artificial or chemically processed products. To respond to this need, and in view of the market opportunity, NutriVita has arrived; an instant powdered drink based on Andean cereals, natural, easy to consume and that helps the development of children and young people in stage of growth and maturity. The product is presented in a PET package, with zipper and easy to use, with presentations of 200 and 400 grams and in chocolate flavor; it can be found in supermarkets in Metropolitan Lima and through authorized distributors. The target of the product are people in segments B and C who shop in supermarkets and who are interested in a better diet for their family and have a healthy lifestyle; Thus, the main shopper of the product will be the parents, while the final consumer are children and adolescents between 6 and 17 years. For the demand calculation of the project, the apparent internal demand of the category of chocolate drinks at the national level was studied and through the geographic, demographic, psychographic and behavioral segmentation, through surveys, the final demand for the products was projected for the years of project life. As a result, the demand obtained for the first year of the project is 127.776 kilograms. It was possible to find the most optimal location for the plant in the district of Ate, located in the East zone of Metropolitan Lima, due to the proximity to the final market and the facility to have good facilities. However, it was detected that the bottleneck in the production process is given by the hammer mill, which as a limiting process will allow the production of 323.357 kilograms. In addition, it is known that the minimum production to start generating profits is 140.827 units of 200 grams and 164.298 units of 400 grams, which together represent 93.884 kilograms. In the plant, to ensure the quality of the final product and the process, controls will be made on the raw materials, during the process and to the finished product; In addition, the HACCP plan will be implemented and Good Manufacturing Practices xiv (GMP) will be adopted. The processes and regulations of the law will be followed and the Sanitation Standard Operating Procedures (SSOPs) will be complied. Also, the environmental impact of the activities of the plant in society and regulations of health and safety at work will be taken into account. Finally, the project was evaluated economically and financially, obtaining positive results, making it profitable to invest in the project; which, with an initial investment of S/. 2.473.712, financed 40% by a bank and 60% by own capital, will result in an Economic NPV equal to S/. 292.020 and Financial NPV of S/. 460.811. In addition, the values of the Economic IRR (19,8%) and Financial IRR (23.3%) are higher than the opportunity cost of capital (COK = 16,67%).